Kajian Proses Pengolahan Garam Beryodium pada Usaha CV. Polewali Jaya Palla di Kecamatan Katobu, Kabupaten Muna - Waode Aisyah; Dhian Herdhiansyah; Weka Gusmiarty Abdullah (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
This study aims to determine the process of processing iodized salt in CV. Polewali Jaya Palla in Katobu District, Muna Regency. This research was conducted intentionally (with a purpose). The types and sources of data used in this study are primary and secondary. Research data collection techniques include (a) interviews; (b) literature studies; (c) documentation; and (d) observation. Data analysis techniques used in descriptive analysis. The results showed that the stages in the processing of iodized salt include: (a) salt washing, (b) salt drying, (c) iodization, and (d) product packaging.